Navigating in the fog. Facing delays, rejection and ignorance when seeking help for primary hyperhidrosis. Issue 1 (1st January 2021) - Shayesteh, Alexander; Gerdsdorff, Fredrik; Persson, Margareta; Brulin, Christine; Nylander, Elisabet
ABSTRACT: Primary hyperhidrosis (PH) is a disease characterized by focal and excessive sweating. Purpose : The aim of this study was to describe the experiences of men and women with PH when seeking help for their condition. Method : A qualitative interview study with 30 men and women diagnosed with PH was conducted. Data was inductively analysed using manifest and latent content analysis. Results : The analysis resulted in a theme: Navigating in the fog, based on the categories doubtful encounters with health care professionals, helpful encounters with health care professionals, delays due to inadequate knowledge, and supported urge for help . Conclusions : Deficient knowledge and understanding about PH create a sense of resignation in individuals, resulting in delay of seeking treatment. Support from others, life-changing events, and finding information about PH were important motivating factors in seeking help and demanding access to treatment. A holistic approach towards patients with PH is important to reduce stigma and acknowledge the problems that are encountered in their daily lives. Educating health care professionals and students so that patients can be identified and assessed without delay and making information available about PH in schools and pharmacies could improve the general knowledge and facilitate obtaining treatment for individuals with PH.